Analisis Perhitungan Dan Penentuan Harga Pokok Produksi Pada PT. Mutifa Medan - John Fisher Gulo; Kamil Mustafa; Ninny Siregar (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2018)
The cost of production is needed to determine the cost of production of a product. Costs incurred to produce the product must be clear, so that the determination of the cost of production would be appropriate. Imprecision in calculating the cost of production will be misleading in making management decisions. Data collection methods used in this study include: Documentation, Interview, Observation. This study analyzed using qualitative descriptive analysis comparing the theory with actual results of the company. PT MUTIFA in determining the cost of production using the full costing method. PT MUTIFA in determining the cost of production, all costs incurred are treated as production costs, both the cost of major raw materials, cost of auxiliary materials, packaging materials costs and production overhead. Classification of production costs in accordance with the theory that exists is composed of material costs, labor costs and production overhead costs. Total production cost per month of each element calculation the average monthly cost is Rp. 73.111.118,260,- and the average number of finished products Paracetamol tablet 500 mg tablet is as much 566,666.67 per month. Based on data on average production costs in 2009, then the production cost per tablet is .Rp. 129,019.